ANALISIS KEHALUSAN BUTIRAN SEMEN SERTA HILANG PIJAR (LOI) PADA SEMEN GEOPOLIMER BERBASIS TANAH NAPA SOLOK - Shasqia, Gea (RC-INSTITUT, 2019)
Cement is a very important material and is widely used in infrastructure development. Therefore the production of cement as a binder increases as well. So it is necessary to look for other materials that can be used as alternative ingredients in making cement. Geopolymer cement is one of the alternative cement breakthroughs synthesized by reacting a material rich in silica alumina with an alkaline activator solution to produce binder binder. The source of silica alumina used is napa soil, because based on the results of XRF analysis carried out by Mawardi (2018) napa soil has a very high content of SiO2 and Al2O3 with a percentage of 63.20% and 16.55% respectively. In this study an analysis of the fineness of cement granules and lost incandescent (LOI) was carried out with variations in the concentration of sodium hydroxide (NaOH) namely 10, 12, 14 and 16 M. Based on the results of this study, it can be seen that the higher the concentration of sodium hydroxide (NaOH) geopolymer cement samples will get harder. Whereas for lost incandescent (LOI) geopolymer samples have a higher content than ordinary cement samples.